Recent Advances of WEE1 Inhibitors and Statins in Cancers With p53 Mutations - Meng, Xiangbing; Gao, Jason Z.; Gomendoza, Sean Michael T.; Li, John W.; Yang, Shujie (Frontiers in Medicine, 2021)
p53 is among the most frequently mutated tumor suppressor genes given its prevalence in >50% of all human cancers. One critical tumor suppression function of p53 is to regulate transcription of downstream genes and maintain genomic stability by inducing the G1/S checkpoint in response to DNA damage. Tumor cells lacking functional p53 are defective in the G1/S checkpoint and become highly dependent on the G2/M checkpoint to maintain genomic stability and are consequently vulnerable to Wee1 inhibitors, which override the cell cycle G2/M checkpoint and induce cell death through mitotic catastrophe. In addition to the lost tumor suppression function, many mutated p53 (Mutp53) proteins acquire gain-of-function (GOF) activities as oncogenes to promote cancer progression, which manifest through aberrant expression of p53. In cancer cells with GOF Mutp53, statins can induce CHIP-mediated degradation of Mutp53 within the mevalonate pathway by blocking the interaction between mutp53 and DNAJA1. Therefore, targeting critical downstream pathways of Mutp53 provides an alternative strategy for treating cancers expressing Mutp53. In this review, we summarize recent advances with Wee1 inhibitors, statins, and mevalonate pathway inhibitors in cancers with p53 mutations.